Басни Эзопа в переводах Л. Н. Толстого - Эзоп (Приокское книжное издательство, 1974)
Экземпляры: РК (20240209) / Инвентарный номер: 1128307 / Сис.шифр: 84(0) / Авт.знак: Э 29 / ГРНТИ: 17 / ББК: 84(0)321-5